2020
DOI: 10.1001/jamaoto.2020.1170
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Multimodal Analgesia Administration and Perioperative Opioid Requirements in Patients Undergoing Head and Neck Surgery With Free Flap Reconstruction

Abstract: IMPORTANCEThe opioid epidemic has reignited interest in opioid-sparing strategies in managing pain. However, few studies have focused on opioid use during perioperative care in patients undergoing head and neck surgery with free flap reconstruction.OBJECTIVES To examine the association between multimodal analgesia (MMA) administration and perioperative opioid requirements in patients undergoing head and neck surgery with free flap reconstruction and to investigate whether MMA alters the duration of stay in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…Nine of 10 studies 16-24 (n = 1151) used an 11-point numerical scale to assess pain, including the visual analog scale (VAS) (6 studies, 16,20-24 n = 774) and the Defense & Veterans Pain Rating Scale (DVPRS) (1 study, 17 n = 65) ( Table 4 ). There was wide variation in subjective pain outcomes among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of 10 studies 16-24 (n = 1151) used an 11-point numerical scale to assess pain, including the visual analog scale (VAS) (6 studies, 16,20-24 n = 774) and the Defense & Veterans Pain Rating Scale (DVPRS) (1 study, 17 n = 65) ( Table 4 ). There was wide variation in subjective pain outcomes among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal and screening by abstract and title, 66 full-text articles were assessed with 10 studies ( 2RCTs, 1 open-label trial, 7 matched cohort studies) meeting inclusion criteria (Table 1). [15][16][17][18][19][20][21][22][23][24] A total of 1253 patients were included with 594 patients in the MMA group and 659 in the non-MMA group. Using weighted averages, the overall population was 62.0 6 5.4 years old and 68.6% male (MMA, 61.0 6 6.0 years, 69.2% male; non-MMA, 62.9 6 4.6 years, 68.0% male) with no difference between the 2 groups.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few publications studying the use of MMA protocols in head and neck cancer surgery with free flap reconstruction. Vu et al demonstrated reduced opioid use intra-operatively and in the post-anesthesia care unit (PACU) when patients were administered pre-operative oral celecoxib, gabapentin, and/or tramadol hydrochloride [ 13 ]. This study, however, did not investigate opioid use after the patients were discharged from PACU.…”
Section: Discussionmentioning
confidence: 99%
“…MMA reduces opioid consumption and may reduce opioid-related side effects [ 11 , 12 ]. A recent study by Vu et al showed MMA was effective in reducing opioid consumption in the post-anesthesia care unit (PACU) in patients undergoing major head and neck surgery [ 13 ]. Many current MMA regimens for head and neck cancer surgery patients recommend the combined use of non-steroidal anti-inflammatories (NSAIDs) and/or COX-inhibitors, and paracetamol.…”
Section: Introductionmentioning
confidence: 99%